Review of Concept of Agni in Ayurveda - Namrata Chouragade; Bharat Chouragade; Anita Wanjari; Sanika Kalambe; Roshan Jha (Indian Journal of Forensic Medicine & Toxicology, 2021)
The term Agni is used in the sense of digestion of food and metabolic products. So it is the great source of energy in universe as well as in the body. Ingested food is to be digested, absorbed and assimilated, which is essential for the maintenance of life and is performed by Agni in Ayurveda. Agni converts food in the form of energy, which is responsible for all vital function of the body. About the importance of Agni, Acharya Charaka has mentioned that the individual dies after stoppage of the function of Agni, and when the Agni of an individual is in equilibrium state, then person is healthy and would lead a long, happy and enjoying disease free life. But, if the Agni of a person gets disturbed by any means, the whole metabolism would be disturbed, resulting in ill health. Hence, Agni is said to be the base (mool) of life. Out of thirteen types of Agni, viz,- one Jatharagni, seven Dhatwagnis and five Bhutagnis, Jatharagni is the leading one controlling all other kinds through its power.